Optimización del proceso de elaboración de queque utilizando harina de tarwi (lupinus mutabilis) - Dionicio Hernández, Dilmer (2015)
Whit the objetive to develop a cake based on lupine flour (Lupinus mutabilis) using response surface method; this research was conducted. The independent variables were replacement percentage lupine flour (3 to 21%) and baking temperature (100 to 170 ° C); taking as the response variable overall acceptability. The most appropriate values of process variables determined by the optimization method by experimental designs; using a central composite design a rotational design 22 including 4 axial and 3 central; which yielded the models that define the behavior of the variables. The only model with a highly significant (p <0.05) was for the baking temperature by having a high coefficient of determination (R2) of 86.2%, making it possible to build the response surfaces for this STATISTICA 7.0 software was used. General acceptability of optimal cake (score 7-7.8) was obtained when substituted between 9 and 12% lupine flour and a bake temperature between 135 ° C to 140 ° C for 30 minutes.